SỰ CẦN THIẾT PHẢI BẢO TỒN ĐA DẠNG SINH HỌC THẢM THỰC VẬT RỪNG NGẬP MẶN KHU VỰC XÃ LONG SƠN, THÀNH PHỐ VŨNG TÀU - Tuấn, Lê Xuân (Trung tâm Nghiên cứu Tài nguyên và Môi trường, 2016)
The biologically high-yielding mangrove ecosystem, which is characteristic in tropical and subtropical waters, not only brings economic benefits, but also plays a major role in regulating climate. It does this by saving and decomposing pollutants, thereby cleaning the marine environment, by acting as a bulwark against wind and storms, by limiting erosion and maintaining silt, thereby mitigating the effects of rising sea levels or even creating conditions for land encroachment into the sea. Like in many other coastal localities of Vietnam, mangrove vegetation in the area of Long Son commune, Vung Tau City, is strongly affected by the pressure of population, economic activities, industrial waste and, above all, the uncontrolled development of shrimp ponds. Lying in the region are many industries, and disputes often occur regarding the benefits or otherwise of the exploitation of natural resources, so the mangroves here are at risk of disruption and decline both in terms of quality and area, and attracts very little investment and interest. In this report, we provide information related to biodiversity, the mangrove flora in Long Son commune and threats to this ecosystem. Some very rare mangrove species, at risk of disappearing from the region, have also been discovered in the mangrove ecosystem of Long Son commune.